No Homo: Gendered Dimensions of Homophobic Epithets Online. - Pascoe, C. J.; Diefendorf, Sarah (Sex Roles, 2019)
We examine a case of homophobic language online, specifically the deployment of the phrase "no homo," shorthand for "I'm not a homosexual." An analysis of 396 instances (comprising 1061 individual tweets) of the use of the phrase "no homo" on the social media platform Twitter suggests that the phrase is a gendered epithet that conveys cultural norms about masculinity. The first finding is that the phrase is used more often by male tweeters than by female tweeters. The second, as predicted by the literature on homophobia, is that the phrase is used in a negative emotional context to convey disapproval for men's homosexuality or behavior that is not gender normative. The third finding is that the modal use of the phrase "no homo" is in a positive emotional context, accompanying expressions of men's pleasure, desire, affection, attachment, and friendship. Our analysis suggests that the phrase "no homo" is a gendered one, primarily used by men to facilitate a particularly masculinized construction of positive emotional expression. Our research adds to and complicates findings on the relationship between homophobia and masculinity that suggests that homophobia is an organizing principal of masculinity in western cultures.